(untitled) (Scientific journal of the Fergana State University, 2023)
This article provides information about the "Travel" genre. A linguopoetic and linguocultural analysis of the poet Khayratiy’s work "Travel" is carried out. The role of cultural words, the meaning of them in the text are discussed in “Travel” work. Cultural lexical units are separated and analyzed one by one. Classical literary words between poetic lines are defined. The article deals with the theoretical issues of text analysis. The important aspect of this research work is that the works of the poet Hayrati are still not sufficiently studied by literary scholars and linguists.